A quasi-in-situ EBSD study on mechanical response and twin variant selection of a hot-rolled AZ31 magnesium alloy - Huicong Chen; Chenwei Shao; Lijun Wang; Hao Chen; Yu Zou (Journal of Magnesium and Alloys)
The selection of twin variants plays a critical role in shaping the deformation texture and mechanical properties of magnesium alloys that are limited by slip systems and diverse twinning modes. In this study, we investigated the twin variant selection and the effect of twinning activity on the strain hardening of a hot-rolled AZ31 magnesium alloy by quasi-in-situ EBSD. Moreover, the Schmid factors and the displacement gradient tensors were computed to evaluate the activation of twin variants. The results reveal that the yield strength increased progressively after each deformation step, driven by grain subdivision and texture hardening induced by extension {101¯2} twinning and the Basinski effect at large strains. The nucleation and growth of the {101¯2} twins occurred either sequentially or simultaneously during the plastic deformation. At low plastic strains, the activation of most twin variants followed the high Schmid factor criterion while the other twin variants with lower Schmid factors were activated due to the interactions with preexisting twins characterized by high misorientation angles (around 60°). Additionally, this non-Schmid factor scenario was also attributed to low coordinated strain requirements from neighboring grains, showing the critical role of local deformation accommodation in the twinning process. These findings advance the fundamental understanding of the twin variant selection and its implications for the microstructure-property relationship in magnesium alloys for structural applications.